Using chemical compositions of sediments to constrain methane seepage dynamics: A case study from Haima cold seeps of the South China Sea. (December 2018) - Wang, Xudong; Li, Niu; Feng, Dong; Hu, Yu; Bayon, Germain; Liang, Qianyong; Tong, Hongpeng; Gong, Shanggui; Tao, Jun; Chen, Duofu
Graphical abstract: Highlights: Sediments from Haima cold seeps have variable compositions. AOM caused high δ 34 SCRS and low δ 13 CTIC values, and high CRS contents. AOM indicators of sediments are variable under variable methane flux and duration. Three methane release events were identified in the seep site. Abstract: Cold seeps frequently occur at the seafloor along continental margins. The dominant biogeochemical processes at cold seeps are the combined anaerobic oxidation of methane and sulfate reduction, which can significantly impact the global carbon and sulfur cycles. The circulation of methane-rich fluids at margins is highly variable in time and space, and assessing past seepage activity requires the use of specific geochemical markers. In this study, we report multiple sedimentary proxy records for three piston gravity cores (QDN-14A, QDN-14B, and QDN-31) from the Haima seep of the South China Sea (SCS). By combining total organic carbon (TOC), total inorganic carbon (TIC), total nitrogen (TN), total sulfur (TS), acid insoluble carbon and sulfur isotope (δ 13 Corganic carbon and δ 34 Sacid-insoluble ), and δ 34 S values of chromium reducibility sulfur (δ 34 SCRS ), as well as carbon isotopes of TIC (δ 13 CTIC ) in sediments, our aim was to provide constraints on methane seepage dynamics in this area. We identified three sediment layers at about 260–300 cm, 380–420 cm and 480–520 cm sediment depth, characterized by particular anomalies of low δ 13 CTIC values and high TS content, high TS and CRS contents, and high δ 34 Sacid-insoluble and δ 34 SCRS values, respectively. On this basis, we propose that these sediment horizons correspond to distinct methane release events preserved in the sediment record. While the exact mechanisms accounting for the presence (or absence) of these particular geochemical signals in the sediment are not known, we propose that they correspond to variations in methane flux and their duration through time. Overall, our results suggest that sedimentary carbon and sulfur and their isotopes are useful tracers for better understanding of methane seepage dynamics over time.